Adoption of mobile applications for identifying tourism destinations by travellers: an integrative approach - Kuo, Tung-Sheng; Huang, Kuo- Chung; Nguyen, Thang Quyet; Nguyen, Phuc Hung (Journal of Business Economics and Management, 2019)
The purpose of the study is to provide an assessment of both how consumers adopt mobile tourism apps and how consumers use those apps to orient customer intentions to visit tourism destinations. The technology acceptance model (TAM) is used to explore customer intentions to adopt tourism apps. A survey of 630 tourism respondents found that the e-servicescape environment and e-word-of-mouth communication play major roles in determining intentions to adopt tourism apps and to visit tourism destinations. Perceived ease of use and perceived usefulness tend to be moderators of the effects of the e-servicescape environment and e-word-of-mouth communication on attitudes towards using apps. The results may be important references to conduct further validations, and critical for marketing managers when designing specific criteria to enhance mobile apps and their adoption. The different managerial implications – including apps to differential marketing tools, improving attitudes towards using tourism apps, and segmenting customers in order to design marketing strategies – are considered.